Effect of Concomitant Elbow Injuries on the Outcomes of Radial Head Arthroplasty: A Cohort Comparison. Issue 10 (October 2017) - Strelzow, Jason A.; Athwal, George S.; MacDermid, Joy C.; Grewal, Ruby; Faber, Kenneth J.; Drosdowech, Darren; King, Graham J.W.
Abstract : Objectives: To compare physical impairments and patient-reported outcomes in patients after simple and complex elbow injuries who were treated with radial head arthroplasty. Design: Prospective. Setting: Quaternary upper extremity referral hospital. Patients/Participants: 148 patients with isolated elbow trauma and no previous injury to the elbow were prospectively enrolled after radial head arthroplasty for an acute unreconstructable fracture. Injury patterns were classified as simple or complex based on the presence or absence of associated elbow fractures and/or dislocation. Intervention: Radial head arthroplasty. Main Outcome Measurements: Patient-Rated Elbow Evaluation (PREE), Disability of the Arm, Shoulder, and Hand, range of motion (ROM), and Biodex measurements. Results: At a minimum 1-year follow-up PREE and Disability of the Arm, Shoulder, and Hand, and ROM and strength values were similar. Forty-four patients evaluated at a mean of 7 years demonstrated no effect of injury pattern on clinical outcomes at any time point. Continued statistical improvements in PREE, supination ROM, and flexion ROM at medium term compared with earlier follow-up were observed. Eight patients required secondary surgery, 2 in the simple injury group and 6 complex injury patients. Conclusions: Concomitant elbow injuries do not affect the longer term outcomes of patients with unreconstructable radial head fractures requiring radial head arthroplasty. Patient outcomes continued to improve beyond 2 years of follow-up. Level of Evidence: Therapeutic Level II. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.